Hair Transplantation Outcomes in Patients with Poor Donor Site Density: Challenges and Innovative Solutions - Kamal Uddin Khan, Farzana Abdullah, Ali Saqlain Saleem, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Hair transplantation remains a cornerstone in the management of androgenetic alopecia and other hair loss disorders. However, patients with poor donor site density pose unique challenges for optimal graft harvesting and aesthetic outcomes. Innovative surgical techniques and donor management strategies have emerged to address this issue, yet limited research has evaluated their efficacy in resource-constrained settings like Pakistan. Materials and Methods: This prospective, observational study was conducted at Bolan Medical Complex Quetta and a private cosmetic center in Islamabad from June 2022 to March 2023. A total of 60 male patients with donor site density <50 follicular units/cm² were enrolled. Two groups were defined: Group A (n=30) underwent traditional FUE (Follicular Unit Extraction) with limited donor management, while Group B (n=30) received advanced planning with body hair integration, micro-grafting, and enhanced extraction angles. Outcomes were assessed using graft survival rate, Global Aesthetic Improvement Scale (GAIS), and FACE-Q questionnaire scores at 6 months postoperatively. Results: Group B demonstrated significantly higher graft survival (82.4% vs. 68.7%, p<0.01), GAIS scores (4.2 ± 0.6 vs. 3.5 ± 0.8, p<0.01), and FACE-Q satisfaction ratings (75.2 ± 9.3 vs. 61.7 ± 11.5, p<0.001). One-way ANOVA confirmed statistically significant differences across all major outcome measures. Moderate positive correlations were observed between donor management complexity and patient satisfaction (r = 0.46, p = 0.002). Conclusion: Innovative donor site strategies, including body hair supplementation and strategic angulation in extraction, significantly improve hair transplantation outcomes in patients with poor donor density. Tailored planning is essential for aesthetic success and patient satisfaction in challenging cases. Keywords: Hair Transplantation, Poor Donor Density, FUE, Body Hair Transplant, Patient Satisfaction, FACE-Q, GAIS